Utilization Of Used Cooking Oil Waste In to Bar Soap As Family Economic Value At KWT Sidomakmur Bandar Lampung City - Serly Silviyanti; Sahrul Ari Irawan (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
epeated use of cooking oil results in the oil becoming used for cooking, and there is still a large amount of used cooking oil that is usually discarded regularly. Naturally, this affects the environment and ecosystem of society related to life. The purpose of this study is to know the process of making bar soap from waste used cooking oil, find out the factors that affect the use of used cooking oil, and know the benefits of used cooking oil as an increase in economic value in the family. The respondents in this study were 5 people who were core members of KWT Sidomakmur, Bandar Lampung City. The location and determination of samples were carried out by purposive sampling and the study was carried out in September 2022